Relationship between cognitive demands and biomechanical indicators associated with anterior cruciate ligament injury: a systematic review - Jiménez-Martínez, J.; Gutiérrez-Capote, A.; Alarcón-López, F.; Leicht, A.; Cárdenas-Vélez, D. (Sports Medicine, 2025)
Background: Anterior cruciate ligament (ACL) injury during contact sports has a high incidence that has not been reduced despite the immense resources devoted to understanding its aetiology. A neurocognitive approach could increase knowledge of the mechanisms contributing to ACL injury enabling practitioners to address and minimise future risk. Objective: To systematically review the influence of manipulating cognitive demands during motor tasks (i.e. degree of uncertainty) on biomechanical variables associated with ACL injury risk. Methods: A systematic review was performed according to the Cochrane Handbook for Systematic Reviews of Interventions by searching the major sporting electronic databases. The search strategy included four groups of terms and was conducted by two authors independently. All studies were screened using unique inclusion criteria, with the included studies assessed for risk of bias. Results: Twenty-five studies were identified from 2031 records and included into the review process. During the experimental conditions where cognitive demands were higher, most biomechanical indicators associated with a greater risk of ACL injury during landing and cutting tasks were significantly enhanced compared with conditions with low or no cognitive demands. Conclusions: An increase in task complexity through cognitive load significantly leads to changes in mechanisms associated with ACL injury during single-leg landings and cutting movements. Consequently, coaches and exercise professionals should consider inclusion of dual-task paradigms or uncertainty during injury risk assessment scenarios and injury prevention programs to help identify athletes at risk of ACL injury and reduce ACL injury frequency.